Development and Validation of HPLC Method for Identification of Ramipril in Printed Tablets and Filaments - V. V. Tihonova; O. A. Terenteva; K. A. Gusev; E. V. Flisyuk; D. N. Maimistov (Разработка и регистрация лекарственных средств, 2022)
Introduction. 3D printing has shown its usefulness as a drug manufacturing technology over the past decade. However, the lack of regulated methods for quality control of finished printed drugs imposes a limitation on the widespread use of 3D printing methods in pharmaceutical practice. Thus, the development of methods for the analysis of printed dosage forms is of interest in pharmaceutical development.Aim. To develop a specific method for the determination of ramipril in filaments and printlets by HPLC.Materials and methods. Substance: ramipril. Excipients: Kollidon® VA 64, Kollidon® CL-F, PEG-1500, sodium carbonate anhydrous, Poloxamer-188, sodium stearyl fumarate. Reagents: hydrochloric acid, acetonitrile for ultra-HPLC, sodium octanesulfonate for HPLC, orthophosphoric acid 85 %, sodium perchlorate analytical grade, triethylamine. Standard: ramipril USP (No 1598303).Results and discussion. A special HPLC method in accordance with an ion-pair reagent (sodium octanesulfonate) for the determination of ramipril in the composition of filaments and printets was proposed.Conclusion. The developed chromatographic method should be adapted for ramipril release determination. This method can be used to quantify ramipril in further studies.